A new proxy signcryption scheme using warrants. (1st January 2011) - Elkamchouchi, Hassan M.; Abouelseoud, Yasmine; Shouaib, Wafaa S.
In this paper, a new proxy signcryption scheme is proposed suitable for use by resource constrained devices such as pagers and mobile phones. The proposed scheme is based on delegating the signing rights of the original signer to one of his proxies using warrants. The use of warrants enables explicit specification of the signing rights of the proxy agent. The proxy agent and the original signer are assumed to be registered within the same traditional public key infrastructure. To offer a higher level of security, the proxy key is derived from the personal key of the proxy signer to prevent the proxy signer from denying a signature it created and protects it from framing attacks mounted by the original signer against it. We also consider a variant of our main scheme that works over elliptic curves since they have proven recently the possibility of reducing the key sizes.